2011
DOI: 10.1523/jneurosci.6153-09.2011
|View full text |Cite
|
Sign up to set email alerts
|

Attention Improves Encoding of Task-Relevant Features in the Human Visual Cortex

Abstract: When spatial attention is directed towards a particular stimulus, increased activity is commonly observed in corresponding locations of the visual cortex. Does this attentional increase in activity indicate improved processing of all features contained within the attended stimulus, or might spatial attention selectively enhance the features relevant to the observer’s task? We used fMRI decoding methods to measure the strength of orientation-selective activity patterns in the human visual cortex while subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
151
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(199 citation statements)
references
References 52 publications
38
151
3
Order By: Relevance
“…However, we found stronger representations of orientation during attend-orientation scans relative to attend-luminance scans in multiple posterior sensory and frontoparietal cortical areas. This finding dovetails with other reports suggesting that featurebased attention can selectively enhance representations of task-relevant features without enhancing representations of taskrelevant features that are part of the same object (Serences et al, 2009;Xu, 2010;Jehee et al, 2011), and demonstrates that featurebased attentional modulations are distributed across the visual processing hierarchy, including regions typically associated with attentional control rather than sensory processing. Traditionally, "sources" and "targets" of attentional control signals have been distinguished on the basis of univariate response properties (e.g., averaged single-unit/population spike rates or averaged fMRI activation).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, we found stronger representations of orientation during attend-orientation scans relative to attend-luminance scans in multiple posterior sensory and frontoparietal cortical areas. This finding dovetails with other reports suggesting that featurebased attention can selectively enhance representations of task-relevant features without enhancing representations of taskrelevant features that are part of the same object (Serences et al, 2009;Xu, 2010;Jehee et al, 2011), and demonstrates that featurebased attentional modulations are distributed across the visual processing hierarchy, including regions typically associated with attentional control rather than sensory processing. Traditionally, "sources" and "targets" of attentional control signals have been distinguished on the basis of univariate response properties (e.g., averaged single-unit/population spike rates or averaged fMRI activation).…”
Section: Discussionsupporting
confidence: 89%
“…Invasive electrophysiological recordings in nonhuman primates (McAdams and Maunsell, 1999;Treue and Martinez-Trujillo, 1999;Martinez-Trujillo and Treue, 2004) and functional neuroimaging studies in humans (Serences and Boynton, 2007;Jehee et al, 2011) suggest that FBA enhances cortical representations of behaviorally relevant visual features in early visual areas. These enhancements are thought to result from top-down feedback signals originating in frontoparietal cortical areas (Serences et al, 2004;Kelley et al, 2008;Greenberg et al, 2010;Zhou and Desimone, 2011;Baldauf and Desimone, 2014;Gregoriou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This modulation may be instantiated by a shift in orientation tuning for neurons in the orientation columns (Kamitani and Tong, 2005;Norman et al, 2006;Jehee et al, 2011), or on a larger cortical scale by changes in radial bias of orientation representation (Sasaki et al, 2006;. Both explanations, however, imply neural changes in the orientation representation in early visual cortex due to action preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it demonstrated that FBA operates in a spatially global way, that is, outside the spatial focus of attention (Maunsell and Treue, 2006). Signatures of global FBA were also documented at the neural population level with fMRI and electromagnetic recordings [electroencephalogram (EEG)/magnetoencephalogram (MEG)] in humans (Saenz et al, 2002;Hopf et al, 2004;Zhang and Luck, 2009;Boehler et al, 2011a;Jehee et al, 2011). For example, Saenz et al (2002) showed that attention to color or motion direction in one visual hemifield increased the BOLD response in striate and extrastriate cortex contralateral to a matching color or motion direction in the unattended visual hemifield.…”
Section: Introductionmentioning
confidence: 94%